2015
DOI: 10.1097/opx.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

Driving Self-restriction and Motor Vehicle Collision Occurrence in Glaucoma

Abstract: Driving self-restriction may be associated with a reduced prevalence of MVCs in men with POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…For example, while some studies have shown that increased severity of glaucomatous visual field loss is linked with elevated state-recorded [8, 10, 11] and self-reported [9, 12] crash rates, as well as poorer open-road driving performance [13], another failed to find a significant association between the extent of glaucomatous binocular field loss and on-road driving performance [14]. Indeed, in the latter study [14], alterations in oculomotor behaviour, particularly through increased glances towards areas of visual field loss, were found to be associated with better driving ability and safety among drivers with glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while some studies have shown that increased severity of glaucomatous visual field loss is linked with elevated state-recorded [8, 10, 11] and self-reported [9, 12] crash rates, as well as poorer open-road driving performance [13], another failed to find a significant association between the extent of glaucomatous binocular field loss and on-road driving performance [14]. Indeed, in the latter study [14], alterations in oculomotor behaviour, particularly through increased glances towards areas of visual field loss, were found to be associated with better driving ability and safety among drivers with glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Another observational study that compared the MVC risk of drivers with and without glaucoma, found that MVC risk was actually lower in those with glaucoma; however, the extent of field loss was not reported and it is possible that drivers with glaucoma may have compensated for their field loss by self‐regulating their driving behaviour. As described above, self‐regulation of driving is associated with reduced prevalence of self‐reported collisions, although this was only evident in the male drivers in that study …”
Section: Glaucomamentioning
confidence: 63%
“…Glaucoma has been associated with a number of self‐reported driving difficulties, including problems with glare, driving at night and tasks requiring peripheral vision and visual search . Self‐reported driving ability is also reduced in drivers with glaucoma who report avoiding challenging driving situations; this is associated with reduced prevalence of self‐reported crashes in men but not women . Importantly, glaucoma is cited as one of the main reasons that older drivers cease driving, with one study reporting that those with bilateral glaucoma were almost three times more likely to cease driving than those without glaucoma …”
Section: Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…35 Ono et al 36 showed that, among 252 glaucoma subjects, 18% avoided driving in fog. However, in a recent study (Correa PC, et al IOVS 2016:57:ARVO E-Abstract 3420), we showed that there is only a relatively weak relationship between subjective concerns about driving ability and objective driving performance in patients with glaucoma.…”
Section: Discussionmentioning
confidence: 99%